Behavior of rectangular concrete-filled high-strength steel tubular columns with different aspect ratio. (December 2016) - Du, Yansheng; Chen, Zhihua; Yu, Yujie
Abstract: High-strength steel members are susceptible to local buckling. Rectangular concrete-filled tubular (CFT) columns could make full use of high-strength steel by restraining its buckling inward. This paper reports an experimental investigation of rectangular CFT columns using high-strength steel. Three current design codes are evaluated with the experiments both from this study and the previous literature. It indicates that EC4, AISC 360 and GB50936 tend to be unsafe incorporating high-strength steel and high aspect ( h/b ) ratio. Design recommendations of the width-to-thickness ( h/t ) ratio are proposed to account for the different h/b ratio effects for rectangular CFT columns. Highlights: New test data for rectangular CFT columns using high-strength steel is provided. Axial behaviors on rectangular CFT columns using high-strength steel are analyzed. Limit of material strength in current codes for CFT columns can be safely extended. Limit of width-to-thickness ratio considering the aspect ratio effect is proposed.